2022
DOI: 10.1021/acsnano.1c09575
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Mapping of a Bacterial Genome with Dual Solid-State Nanopores and Active Single-Molecule Control

Abstract: We present an electronic mapping of a bacterial genome using solid-state nanopore technology. A dual-nanopore architecture and active control logic are used to produce single-molecule data that enables estimation of distances between physical tags installed at sequence motifs within double-stranded DNA. Previously developed “DNA flossing” control logic generates multiple scans of each captured DNA. We extended this logic in two ways: first, to automate “zooming out” on each molecule to progressively increase t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…To date, most re-reading systems are based on symmetric nanopore structures, , where symmetric opening areas are at both sides of the membrane nanopore. This symmetric feature also exists in the two-nanopore system of the same size within the tug-of-war configuration. This symmetry leads to the same recapture behavior for the forward and backward translocation. Our previous study using an asymmetric nanopore demonstrated that DNA polymers showed distinct translocation dynamics in opposite translocation directions, especially in the velocity profiles as a function of time.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…To date, most re-reading systems are based on symmetric nanopore structures, , where symmetric opening areas are at both sides of the membrane nanopore. This symmetric feature also exists in the two-nanopore system of the same size within the tug-of-war configuration. This symmetry leads to the same recapture behavior for the forward and backward translocation. Our previous study using an asymmetric nanopore demonstrated that DNA polymers showed distinct translocation dynamics in opposite translocation directions, especially in the velocity profiles as a function of time.…”
mentioning
confidence: 76%
“…Previous studies have shown that more recaptures can be achieved by minimizing the time interval between the end of the blockade event and the voltage reversal . Alternatively, a molecule may be trapped in a “tug-of-war” by two parallel nanopores or using optical tweezers. In each of these scenarios, the voltage difference between the two pores can be adjusted to shuttle the DNA molecule back and forth, facilitating multiple readings of the resultant signal. To date, most re-reading systems are based on symmetric nanopore structures, , where symmetric opening areas are at both sides of the membrane nanopore.…”
mentioning
confidence: 99%
“…Solid state nanopores, in contrast, have not achieved base-level sensitivity but offer much faster translocation rates and the capability of processing more complex biomolecules, such as higher-order protein and RNA structures and DNA-protein complexes [7]. There has been recent success in developing genomic mapping schemes using solid state nanopores, including through the use of CRISPR [8] and nick-bound oligonucleotide tags [9].…”
Section: Introductionmentioning
confidence: 99%
“…If the molecule translocation is linear (i.e., no folds are present), the feature blockades can also provide information regarding the feature’s binding position with respect to the molecule’s underlying sequence, or the relative distance of the given feature from other features 7 , 10 . For example, molecular features that bind specifically to repetitive sequence motifs (for example, the recognition sequence of nicking endonucleases), produce a barcode that can then be aligned genome scale 15 . In proposed DNA information storage applications, molecular features can be used to represent the position of ‘1’ bits 11 .…”
Section: Introductionmentioning
confidence: 99%